The geopolitics of online taxation in Asia-Pacific digitalisation, corporate tax base and the role of governments - Martina F. Ferracane; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2018)
Governments use taxation as a policy instrument to create a favourable business climate in the face of competition from neighbouring countries. Tech companies appear to be bearing the brunt of the blame associated with this geopolitics of tax, even though it is actually governments who set tax law and determine the international allocation of profit. The prevailing public perception that tech companies pay less corporate taxes is a myth: A comparison of the global effective tax rates (ETRs) paid by some of the world's largest internet firms worldwide shows that they pay taxes which are on average with those of leading businesses across the Asia-Pacific region. In addition, the biggest companies from Silicon Valley pay similar or even higher rates than those paid by many other internet companies in the Asia-Pacific region. The real question is where corporate taxes are paid. Most businesses tend to keep their key functions and production capacities in the country where they were once founded. By extension, they also tend to pay their taxes in that country. If Silicon Valley was to engage in profit shifting, they would be moving their profits in the other direction: To Asia, where the growth rates are higher and corporate tax rates are lower - not vice versa ...
Keywords: 330